Permainan Teka-Teki Silang dalam Pembelajaran Mufradāt di Kelas X IPA MA Irsyadun Nasyi’in - Imam Wahyudi; Siti Rofiqoh (INAIFAS Press, 2021)
Mufradāt is a key component for students to learn in Arabic lessons. The use of crossword puzzles can help students master Arabic vocabulary well. This research aimed to describe the implementation of crossword puzzles in mufradāt learning in class X IPA MA Irsyadun Nasyi'in Jember. This article used qualitative research methods to focus on the process of implementing crossword puzzles in mufradāt learning. Data mining techniques were carried out through documentation. The results of the implementation of crossword puzzles in mufradāt learning showed that 41% of students were found to be classified as very capable, 35% capable, and 24% less capable based on the assessment indicators used. This crossword puzzle game can be a challenging Arabic learning style for students in mastering Arabic mufradāt.